Novel functional nanoscale composites on the basis of oligoperoxide surfactants: synthesis and biomedical applications - Zaichenko, O.; Stoika, R.; Mitina, N.; Lutsik, M.; Shevchuk, O.; Lobaz, V.; Boiko, N. (Інститут біохімії ім. О. В. Палладіна НАН України, 2008)
Principal experimental approaches based on tailored synthesis of oligoperoxide surfaceactive substances and their application for obtaining polymeric and hybrid nanoscale carriers possessing targeted functionality and biocompatibility are presented. Molecular design of novel linear, block and comblike oligoperoxide surfactants and derived coordinating complexes of transitional and rare earth metal cations is a convenient tool for synthesis of luminescent, magnetic and other functional nanocomposites with controlled size distribution, functionality, reactivity and biocompatibility. The methods developed provide combining the stage of formation of polymeric, metal and metaloxide nanoparticles with the stage of their surface irreversible modification by functional surfaceactive oligoperoxides capable of binding physiologically active substances. The availability of reactive ditertiary peroxide fragments provides a possibility for functionalization of developed nanoparticles that were applied for studying phagocytosis, surface markers of pathological cells, and targeted delivery of drugs and antimicrobial remedies.